Resolved Scattered Light Images of the Edge-On Protoplanetary Disk ESO Hα 569. Issue Volume 8:Issue S299(2013) (6th January 2014) - Wolff, S.; Perrin, M.; Stapelfeldt, K.; Duchêne, G.; Krist, J.; Ménard, F.; Padgett, D.; Pinte, C.
Abstract: We present detailed models of the edge-on protoplanetary disk ESO Hα 569 (SSTgbs J111110.7-764157) from resolved scattered light images from HST and a complete spectral energy distribution. Data was obtained as part of an HST campaign to catalogue edge-on disks around young stars in nearby star forming regions (HST program 12514, PI: Karl Stapelfeldt). We confirm that this object is an optically thick edge-on disk around a young star with an outer radius of 125 AU. Using full radiative transfer models, we probe the distribution of dust grains and overall shape of the disk (inclination, scale height, dust mass, maximum particle size, inner radius, flaring exponent and surface/volume density exponent).